A study of the occurence & condition of the third molars among the U.P. College of Dentistry students 1979-1980 - Fider Jr., Alejandro; Moran, Juan Sebastian; Marquez, Eleuteria (Adviser).; Jimena, Edna M. (Adviser)+.
130 dental students of U.P.C.D. who are at least 60% Filipino by race, with an age range of 18-27 were examined clinically and radiographically to determine the occurance, distribution and classification of their third molars. The results of the study revealed that 79% of the subjects have one or more third molars with an average of 3.15/student and 21% do not have third molars at all. Of the erupted third molars examined, 81% are malposed, while 82% of the unerupted third molars examined are impacted. There is a tendency for the maxillary third molars to position bucally and for the mandibular to tilt mesially and lingually. No correlation between third molar malpositioning and crowding of teeth in the same quadrant was observed. Finally, a correlation was found in the study with regards to the evolutionary disappearance of the third molars, though more studies of similar nature may be necessary to make conclusive correlations.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.